Import penetration and manufacturing employment growth: Evidence from 12 OECD countries - Sebastian Köllner (Julius Maximilian University of Würzburg, Chair of Economic Order and Social Policy, 2016)
This paper investigates the relationship between growing import penetration and manufacturing employment growth in 12 OECD countries between 1995 and 2011, accounting for various model specifications, different measures of import penetration and alternate estimation strategies. The application of the latest version of the World Input-Output Database (WIOD) that has become available only recently allows to measure the effect of increasing imported intermediates according to their country of origin. The findings emphasize a weak positive overall impact of growing trade on manufacturing employment. However, intermediate inputs from China and the new EU members are substitutes to manufacturing employment in highly developed countries while imports from the EU-27 act as complements to domestic manufacturing production. A three-level mixed model implies that the hierarchical structure of the data only plays a minor role, while controlling for endogeneity leaves the results unchanged.
Keywords: E24; F16; J23; L60; 330; Import Penetration; Manufacturing; Labor Markets; Hierarchical Mixed Model